A STUDY ON PRACTICAL APPLICATIONS OF ACCOUNTING AND FINANCIAL MANAGEMENT CONCEPTS AT JSW STEEL - Kohli, Simran; Kulkarni , Sameer A; Sharma, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
This paper intends to understand the practical applicability of some of the accounting and financial management concepts in large industrial organizations, with special reference to JSW Steel, one of the leading producers of steel in India. The need for this study is to bridge the gap between theoretical learning from classrooms and the actual implementation of financial practices in a corporate setup. Students and interns totalling 45 were surveyed in a structured manner to assess their understanding and experience of practical accounting and financial management during their internship programs. The findings thus show that though students know that these things are important, they cannot apply them properly in real life because of limited exposure, short duration of internships, and restricted access to company data. This study also finds that JSW Steel depends on modern software systems like Tally, SAP, and ERP for ensuring accounting accuracy and financial transparency. This paper concludes that increasing the duration of internship, mentorship programs, and practical workshops can significantly improve the learning experience of the students and subsequently prepare them for professional careers in finance.